Platelet-monocyte aggregates: molecular mediators of thromboinflammation - Rolling, Christina C.; Barrett, Tessa J.; Berger, Jeffrey S. (Frontiers in Cardiovascular Medicine, 2023)
Platelets, key facilitators of primary hemostasis and thrombosis, have emerged as crucial cellular mediators of innate immunity and inflammation. Exemplified by their ability to alter the phenotype and function of monocytes, activated platelets bind to circulating monocytes to form monocyte-platelet aggregates (MPA). The platelet-monocyte axis has emerged as a key mechanism connecting thrombosis and inflammation. MPA are elevated across the spectrum of inflammatory and autoimmune disorders, including cardiovascular disease, systemic lupus erythematosus (SLE), and COVID-19, and are positively associated with disease severity. These clinical disorders are all characterized by an increased risk of thromboembolic complications. Intriguingly, monocytes in contact with platelets become proinflammatory and procoagulant, highlighting that this interaction is a central element of thromboinflammation.